PARE0003 The Effect of Exercising in Warm Water – Seen from the Perspective of the Patients. (10th June 2014) - Jacobsen, M.; Mindegaard, P.
Abstract : Background: In Denmark one in eight of the population, has one or more rheumatic diseases causing pain and decreased physical function in everyday life. Exercising in warm water pools has become a very popular and healthy activity among many members of the Danish Rheumatism Association. In recent years there has been an increased focus on public expenses associated with the operation of the swimming facilities and several public pools have been closed down. The health authorities want people with arthritis to carry out their exercise on land instead of in warm water as it is associated with lower costs. In order to change development The Danish Rheumatism Association took the initiative to make a study in collaboration with researchers from the University of Southern Denmark. Objectives: The purpose of the study is to examine why patients with arthritis prefer exercise in warm water. Methods: The design of the study is a semi-structured questionnaire targeted among patients with arthritis who exercise once a week in warm water. As part of the study a number of qualitative interviews were carried out in addition among the participants. The activity is organized through evening classes. The survey was conducted among participants of 38 evening classes run by the Danish Rheumatism Association. 2, 384 questionnaires were sent by mail to the managers of the classes and distributed to the participants. 1431 questionnaires were returned, which is a response rate of 60%. The interviews were based on 4 focus groups with 17 participants. Results: The study shows that the typical participant is between 60-79 years of age (70%) and 87% of the participants were women. – 2% estimate their health to be very good and 31% to be good – 52% estimate their health fairly good and 12% estimate their health to be bad and very bad. The most common medical condition among participants is a spectrum of different kinds of rheumatic diseases and common comobidity is cardiovascular diseases, diabetes and respiratory diseases. – 79% of the participants answered that exercise in warm water gives them better strength, flexibility, endurance and balance. – 72% answered that exercise in water gives them increased mobility – 64% experienced pain relief – 58% said that exercising in warm water enables them to cope with various daily tasks. – 45% said that exercising in warm water gives them a greater mental well-being. Many participants report that exercising in warm water is the only kind of exercise they are able to do because of their physical disability and the participants seem to use the exercising as a part of their rehabilitation or as a way to, maintain their physical function and mental well-being. Conclusions: The typical participant is between 60-79 years of age (70%). 87% of the participants are women. The study shows that people with arthritis join classes in warm water pools in order to strengthen their muscles, mobility, balance for and decrease pain. They have often tried other kinds of exercise on land without success because their physical disability. The participants view the exercising in water as part of their rehabilitation or as a way to maintain their physical function. Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.3189